INOVASI PENGAJARAN REBAB SUNDA MELALUI METODE DRILL: IMPLEMENTASI DAN ANALISIS EFEKTIVITAS - Tresnadi, Soni; Wastap, Jaeni B (JURNAL EDUCATION AND DEVELOPMENT, 2025)
This article aims to reveal the learning of Sundanese rebab playing using drill method by Asep Mulyana to art academics and public. The lack of research on how the drill method is used in teaching rebab is the basis for writing this article. The research method is qualitative research method based on data collection from literature study, observation, interview and documentation. The result of this research, it can be concluded that the drill method of learning to play Sundanese rebab by Asep Mulyana involves a practical approach through repeated practice to get maximum skill, observation, and emphasis on creativity and improvisation. Although humans get direct learning and experience, but they learn more from observing other people's behavior and repetition to get maximum skill. This method allows the learner to not only achieve the desired technique of playing Sundanese rebab, but it can also help the learner to understand the musical sense contained in Sundanese rebab playing.